Biochar-based fertilizer increases soil nutrients and enhances tea quality: a metabolomics-based analysis - Zhenyu Yang; Zetao Ren; Xiangzhen Zhu; Wenyan Yang; Zhengqian Ye; Luming Tian; Jiawei Ma (Frontiers in Plant Science)
IntroductionBiochar-based fertilizers (BF) have emerged as a promising strategy to improve soil physicochemical and biological properties, thereby enhancing tea yield and quality.MethodsA field experiment was conducted using two types of BF- ordinary BF (BF1, containing 15% biochar) and optimized BF (BF2, containing 30% biochar)- applied for either 1 or 2 years. The effects on the soil nutrients, tea plant growth, tea quality, and metabolomics profiles were assessed.ResultsResults showed that BF application significantly increased soil pH and nutrient availability, as well as the bud length and hundred-bud weight (p < 0.05). Notably, BF2 applied for 2 years significantly increased the content of free amino acids, total flavonoids, soluble sugar, while reduced the phenol-ammonia ratio (p < 0.05), thereby improving tea quality. Further metabolomics analysis revealed that BF2 treatment significantly elevated the levels of amino acids, including theanine, threonine, proline, valine, and glutamic acid, while decreasing catechins including C, EC, and EGCG, thus leading to reduced bitterness and astringency and enhanced freshness. Besides, differential metabolites were mainly involved in amino acid and flavonoid biosynthesis pathway.DiscussionTaken together, prolonged BF2 application significantly improved soil fertility, promoted tea growth, and enriched flavor-related metabolites, offering valuable insights for optimizing fertilization strategies in tea plantations.